INSTIs-centered antiviral regimens for first-line treatment of HIV/AIDS: a network meta-analysis and cost-effectiveness analysis - Jian Yang; Xuejuan Zhao; Fan Li (BMC Infectious Diseases)
Abstract Objective This study evaluates the efficacy, safety, and cost-effectiveness of INSTI-based antiretroviral regimens compared to the national standard first-line treatment EFV/3TC/TDF for HIV/AIDS in China. The aim is to guide clinical decision-making and improve HIV/AIDS prevention and treatment. Methods A network meta-analysis was conducted using ADDIS software on data from domestic and international randomized controlled trials comparing INSTI-based regimens with EFV/3 TC/TDF. Additionally, a Markov model assessed the cost-effectiveness of the representative INSTI regimen B/F/TAF (Bictegravir/Emtricitabine/Tenofovir Alafenamide) against EFV/3 TC/TDF. Costs and health outcomes were measured in US Dollars ($) and Quality-Adjusted Life Years (QALYs), respectively, evaluating incremental cost-utility ratios (ICERs) against a willingness-to-pay threshold of 1.5 times GDP per capita. Results Seventeen trials involving 12,620 patients were analyzed. INSTI regimens showed no significant efficacy or safety advantages over EFV/3 TC/TDF but offered better drug resistance, adherence, and quality of life improvements. Economic analysis from the patient perspective showed that B/F/TAF had an ICER of $12,714.29/QALY, which is below the willingness-to-pay threshold, indicating cost-effectiveness. From the healthcare system perspective, B/F/TAF's ICER was $23,052.77/QALY, which is above the threshold, suggesting it is not cost-effective from this perspective. Sensitivity analyses confirmed these findings, with drug costs for B/F/TAF and the probability of CD4 count increase post-EFV/3TC/TDF treatment being the largest influencing factors. Additionally, probabilistic sensitivity analysis indicated that B/F/TAF has a varying probability of economic viability depending on the willingness-to-pay threshold, highlighting its potential value in specific economic contexts. Conclusion INSTI-based regimens are as effective and safe as the national standard but offer additional benefits in drug resistance and patient compliance. B/F/TAF is economically viable from the patient perspective but does not present a cost-utility advantage from the healthcare system perspective. This study underscores the need for considering both clinical and economic factors in selecting first-line HIV/AIDS treatments in China.